2019
DOI: 10.1007/s10869-019-09633-y
|View full text |Cite
|
Sign up to set email alerts
|

Be(com)ing Real: a Multi-source and an Intervention Study on Mindfulness and Authentic Leadership

Abstract: Although authentic leadership has been shown to inform a host of positive outcomes at work, the literature has dedicated little attention to identifying its personal antecedents and effective means to enhance it. Building on strong theoretical links and initial evidence, we propose mindfulness as a predictor of authentic leadership. In 2 multi-source field studies (cross-sectional and experimental), we investigated (a) the role of leaders' trait mindfulness and (b) the effectiveness of a low-dose mindfulness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 112 publications
(233 reference statements)
3
48
0
1
Order By: Relevance
“…While trait mindfulness has mostly been studied in disciplines such as psychology, neuroscience, and medicine, a small but growing number of organizational studies have begun to explore its potential benefits in the workplace context (Good et al, 2016). For example, it has been shown that trait mindfulness positively relates to psychological health (Kiken et al, 2017), job performance (Dane & Brummel, 2014), prosocial behavior (Donald et al, 2019), transformational leadership (Carleton et al, 2018; Pinck & Sonnentag, 2018), and authentic leadership (Dietl & Reb, 2019; Nübold et al, 2019). Another cluster of research explores the interpersonal effects of leader mindfulness on followers.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…While trait mindfulness has mostly been studied in disciplines such as psychology, neuroscience, and medicine, a small but growing number of organizational studies have begun to explore its potential benefits in the workplace context (Good et al, 2016). For example, it has been shown that trait mindfulness positively relates to psychological health (Kiken et al, 2017), job performance (Dane & Brummel, 2014), prosocial behavior (Donald et al, 2019), transformational leadership (Carleton et al, 2018; Pinck & Sonnentag, 2018), and authentic leadership (Dietl & Reb, 2019; Nübold et al, 2019). Another cluster of research explores the interpersonal effects of leader mindfulness on followers.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Relating to one's experiences with curiosity, openness and acceptance has been proposed to spark creativity, open new perspectives, enhance problem-solving, and facilitate coping with uncertainty (Baas et al 2014;Jacobs and Blustein 2008;Lebuda et al 2016;Ostafin and Kassman 2012). These intrapersonal qualities might positively affect interpersonal functioning (Moll et al 2015) and leadership behavior (Nübold et al 2019;Reb et al 2019;Schuh et al 2019). Thus, workplace mindfulness is expected to improve not only individual well-being and performance but also the productivity, agility, and innovative strength of organizations on the whole (Greiser and Martini 2018).…”
mentioning
confidence: 99%
“…(2018) pointed out that core aspects of AL, such as the consistency of thoughts and behaviours, cannot be evaluated by other persons (see also Hewlin, Dumas and Burnett, 2017; Knoll et al ., 2015). Research found significant positive correlations between leader and follower ratings of AL (Nübold, van Quaquebeke and Hülsheger, 2019). Also, the level of granularity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, we followed recommendations for data screening to enhance quality (DeSimone and Harms, 2018; DeSimone, Harms and DeSimone, 2015). Future longitudinal research could study different forms of dynamics in AL behaviour, such as growth through interventions (Nübold, van Quaquebeke and Hülsheger, 2019), and include follower outcomes in response to short‐term fluctuations of AL (Gill and Caza, 2018) as well as carry‐over effects on following days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation